Uncertainty Avoidance and the Rate of Business Ownership across 22 OECD Countries, 1976-2000 - Sander Wennekers; Roy Thurik; André van Stel; Niels Noorderhaven (Tinbergen Institute, 2003)
This paper deals with the influence of cultural attitudes towards uncertainty on the level of businessownership across countries. First, the concepts of uncertainty and risk are elaborated, as well as theirrelevance for entrepreneurship. Second, cross-sectional regression analysis using data for three separateyears in twenty Western countries and Japan and controlling for GDP per capita, yields evidence thatuncertainty avoidance is positively correlated with the prevalence of business ownership. This surprisingfinding suggests that a personal trait (risk aversion) and its related cultural characteristic (uncertaintyavoidance) may have a diverging impact on entrepreneurship. Possibly, a climate of uncertainty avoidancein large organizations pushes enterprising individuals towards self-employment. Third, we carry out pooledpanel regressions with respect to business ownership rates in two distinct cultural country clusters for theyears 1976, 1988 and 2000. In the group of high-uncertainty avoidance countries a strongly negativerelationship between GDP per capita and the level of business ownership is found, suggesting that risingopportunity costs of entrepreneurship are the dominant perception in this cultural environment. In a groupof low-uncertainty avoidance countries no such influence of per capita income is found, but the profitsassociated with being self-employed are positively associated with business ownership.
Keywords: P52; M13; 330; comparative analysis of economies; cultural economics; entrepreneurship; macro-economic analyses of economic development; Entrepreneurship-Ansatz; Risiko; Wirtschaftssoziologie; Vergleich; OECD-Staaten